In Vitro Antibacterial Activity of Essential oil and Ethanolic Extract of Ajowan (Carum Copticum) against some Food-Borne Pathogens - Alireza Mohammadzadeh (Journal of Global Pharma Technology, 2017)
The present study aimed at evaluating the in vitro antibacterial activity of essential oil and ethanolic extract of ajowan (Carum copticum) against some food-borne pathogens.The micro-dilution method was used to study the antibacterial activity of ajowan (Carum copticum) essential oil and ethanolic extracts against some food-borne pathogens (Bacillus cereus, Staphylococcus aureus, Salmonella typhimurium and Escherichia coli ). The ethanolic leaf extract of ajowan against Salmonella typhimurium strain showed the best antibacterial activity, with the lowest minimal inhibitory concentration (MIC) of 50 mg ml-1 and MBC was 100 mg ml-1 for this bacterium and the results of essential oil on all bacteria tested showed that gram-negative bacteria were sensitively. MIC and MBC of essential oil for Salmonella typhimurium were 16 and 32 mg ml-1 respectively and MIC for Escherichia coli was 32 mg ml-1. According to results, the essential oil and ethanolic extract of this plant has antibacterial activity and therefore it could be used as a natural preservative ingredient in food and/or pharmaceutical industries.Keywords: ajowan (Carum copticum), essential oil, ethanolic extract, antibacterial activity